A Semiotics Analysis of Characters in Spongebob Movie: Sponge on The Run (2020) - Hasibuan, Novia Anggita; Damanik, Sisila Fitriany (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
This study is about discusses semiotic meaning of the characterizations in SpongeBob Movie: Sponge on the Run (2020) using Roland Barthes' theory. The data was taken from screenshots of the characters that contained semiotic meaning. The researcher found 64 pictures that have been analyzed there were 10 data from SpongeBob, 9 data from Patrick, 8 data from Mr.Krabs, 8 data from Squidward, 6 data from Plankton, 6 data from Sandy, 4 data from Gary, 7 data from King Poseidon, 4 data from Sage and 2 data from Otto. This research uses descriptive qualitative method. The results of this study state that the type of semiotics by Barthes can be used to explain the characters meaning of semiotics contained in it. The type of Barthes Semiotics in this film also has different meanings in describing something according to the action or behavior contained in the film scene.